Tourism in Kuakata: A Curbed Rareness in Global Village - Horaira, Mohammad Abu (American Journal of Trade and Policy, 2018)
Kuakata, locally called as ‘Sagor Konnya’ (Daughter of the Sea) is located in the southernmost tip of Bangladesh and is one of the most rare tourism destinations having the exceptional view of the rising and setting of the crimson sun in the water of the Bay of Bengal. Perhaps that makes Kuakata one of the world's unique beaches. After reviewing the literature and different sources related to tourism, it is being found that there is very little attention given to Kuakata as an exclusive tourism destination. The paper is based on secondary data sources like-articles, journals, websites of the target tour operators and authorities. For the globalization of tourism, it is essential to provide background information about the destination to the international visitors and Bangladesh is far behind of it. The government, NTOs (National Tourism Organizations), local administration, owners of hotels and motels, private tour operators and travel agencies should work in an integrated approach which can create a positive impression about Kuakata in the tourists’ mind and feels free to visit and recommend others.
Keywords: Kuakata; Rarest; Bay of Bengal; Beach; Tourism; Destination; Globalize; International Visitors; Bangladesh